Mitigating Road Hazards: A Comprehensive Impact Assessment Of Road Accidents And Identification Of Accident-Prone Areas On NH-07 From Rishikesh To Srinagar Garhwal, Uttarakhand (Journal of Namibian Studies : History Politics Culture, 2023)
Road accidents are a significant public health concern, posing serious threats to human life and causing substantial economic losses. This study focuses on NH-07, a crucial highway connecting Rishikesh to Srinagar Garhwal in the northern region of India, with the aim of conducting a comprehensive impact assessment of road accidents and identifying areas prone to accidents. The research employs a multidisciplinary approach, combining statistical analyses, geospatial mapping and community feedback to provide a holistic understanding of the problem. The impact assessment encompasses the analysis of accident data over a specified timeframe, considering factors such as accident severity, types of vehicles involved and contributing factors. Statistical methods and Geospatial techniques have been employed to identify accident hotspots, patterns, trends and correlations within the accident data, facilitating the development of targeted intervention strategies. Additionally, community engagement and stakeholder consultations has been conducted to gather qualitative insights into local perceptions and experiences related to road safety on NH-07. The study's findings will contribute valuable insights for policymakers, transportation authorities and local communities in formulating evidence-based strategies to enhance road safety on NH-07. The identification of accident-prone areas and the factors contributing to accidents will guide the prioritization of resources and interventions, ultimately reducing the frequency and severity of road accidents on this critical highway.